A New Serial-direction Trail Effect in CCD Images of the Lunar-based Ultraviolet Telescope. (13th September 2016) - Wu, C.; Deng, J. S.; Guyonnet, A.; Antilogus, P.; Cao, L.; Cai, H. B.; Meng, X. M.; Han, X. H.; Qiu, Y. L.; Wang, J.; Wang, S.; Wei, J. Y.; et al.
Abstract: Unexpected trails have been seen subsequent to relative bright sources in astronomical images taken with the CCD camera of the Lunar-based Ultraviolet Telescope (LUT) since its first light on the Moon's surface. The trails can only be found in the serial-direction of CCD readout, differing themselves from image trails of radiation-damaged space-borne CCDs, which usually appear in the parallel-readout direction. After analyzing the same trail defects following warm pixels (WPs) in dark frames, we found that the relative intensity profile of the LUT CCD trails can be expressed as an exponential function of the distance i (in number of pixels) of the trailing pixel to the original source (or WP), i.e., exp ( α i + β ) . The parameters α and β seem to be independent of the CCD temperature, intensity of the source (or WP), and its position in the CCD frame. The main trail characteristics show evolution occurring at an increase rate of ∼(7.3 ± 3.6) × 10 −4 in the first two operation years. The trails affect the consistency of the profiles of different brightness sources, which make smaller aperture photometry have larger extra systematic error. The astrometric uncertainty caused by the trails is too small to be acceptable based on LUT requirements for astrometry accuracy. Based on the empirical profile model, a correction method has been developed for LUT images that works well for restoring the fluxes of astronomical sources that are lost in trailing pixels.